Becoming Political: An Expanding Role for Critical Leisure Studies. (27th December 2018) - Rose, Jeff; Harmon, Justin; Dunlap, Rudy
Abstract: This article explores the intersection of politics and leisure, pointing to the fact that power has always been present in leisure activities, settings, practices, and institutions. In noting some of the past contributions of leisure scholarship, it also highlights a need for increasingly political leisure research, where knowledge production, epistemologies, and methodologies help unpack multiple critical leisures. Using engagements with Foucauldian biopolitics, political ecology, and radical political thought, this article sets the stage for the eight manuscripts that engage with critical components of political dimensions of leisure. In light of the pressing catastrophes of our time, we contend that scholars and educators can and should be engaged in building a more critically diverse and intellectually productive academy.